Pancasila sebagai Dasar Nilai Pengembangan Ilmu dan Implikasinya terhadap Etika Ilmuwan - Romadhoni, Nailil Izzah (Maliki Interdisciplinary Journal, 2026)
Pancasila serves as a foundational value system that guides the development of science and technology in Indonesia. This study examines the role of Pancasila as an ethical foundation in scientific activities and its implications for the ethics of scientists through a literature review approach. The findings show that the values of Pancasila function as moral guidelines in upholding honesty, responsibility, respect for human dignity, and research orientation for the common good. In addition, Pancasila acts as a normative filter to ensure that the development of science and technology does not deviate from humanitarian and justice values. The integration of Pancasila’s values is therefore considered capable of strengthening integrity and research ethics. Strengthening institutional policies, integrating Pancasila values ​​into research education, and enforcing scientific codes of ethics must be consistently implemented to ensure scientific progress remains moral and serves the public interest. As a recommendation, more consistent guidance and ethical implementation are needed in research environments to ensure scientific development remains responsible and beneficial to the public.